Implementation of the Economic Empowerment-Based Demonstration Method in Fiqh Learning for Buying and Selling at MA Walisongo Purwosari - Ahmad Nur Said; Ahmad Ma`ruf; Jamhuri Jamhuri; Ali Mohtarom (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This research was made to explain the implementation of the economic empowerment-based demonstration method in learning fiqh chapter of buying and selling at MA Walisongo Purwosari. This research uses a qualitative approach with a case study type of research. Data collection techniques are through observation, interviews, and documentation. The research subjects include Fiqh teachers and students of MA Walisongo Purwosari and data analysis is carried out through summarizing data, presenting data, and drawing conclusions. The results of this study show that the implementation of the demonstration method based on economic empowerment in fiqh learning is carried out through three stages, the first is planning, followed by implementation and closed with learning evaluation. In the planning stage, the researcher compiles learning tools, prepares practical media and designs buying and selling demonstration activities in accordance with Islamic law. At the implementation stage, researchers give examples and students practice, so that students become directly involved in the simulation of buying and selling practices, so that learning is more active. At the evaluation stage, the researcher assesses the success of the understanding received by students during the learning process. The implementation of the demonstration method based on economic empowerment provides satisfactory results for students' understanding of fiqh material on buying and selling, improving practical skills, and fostering Islamic economic values such as honesty, responsibility, and cooperation.